1983
DOI: 10.1104/pp.73.3.630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SO2 and O3 on Allocation of 14C-Labeled Photosynthate in Phaseolus vulgaris

Abstract: There is good evidence that air pollutants may exert significant impacts on plant productivity by altering the partitioning of dry matter between plant parts (10,19,24,25). In addition to altered partitioning of carbohydrates between plant parts, the costs of repair from air pollution as well as disease-related stress may reduce carbohydrates available for growth by increasing the costs of repair of damage to cellular or metabolic systems (11). Studies with several plant species have indicated that the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Several studies have reported decreases in root biomass associated with above-ground exposure to O., with concomitant decreases in root:shoot ratios (Cooley & Manning, 1987;Miller, 1987). These studies, along with C-partitioning studies (mostly on annual species) suggest that the proportion of C allocated to the root system is decreased in O.;-exposed plants (McCool & Menge, 1983;McLaughlin & McConathy, 1983;Gorrisen et al, 1991a). The mechanisms regulating assimilate partitioning in the whole plant are poorly understood (Wardlaw, 1990;GifTord et al, 1984), and although it is recognized that source-sink relationships change with developmental stage (Evans, 1991), assimilate partitioning is also influenced by both endogenous and environmental factors (Patrick, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported decreases in root biomass associated with above-ground exposure to O., with concomitant decreases in root:shoot ratios (Cooley & Manning, 1987;Miller, 1987). These studies, along with C-partitioning studies (mostly on annual species) suggest that the proportion of C allocated to the root system is decreased in O.;-exposed plants (McCool & Menge, 1983;McLaughlin & McConathy, 1983;Gorrisen et al, 1991a). The mechanisms regulating assimilate partitioning in the whole plant are poorly understood (Wardlaw, 1990;GifTord et al, 1984), and although it is recognized that source-sink relationships change with developmental stage (Evans, 1991), assimilate partitioning is also influenced by both endogenous and environmental factors (Patrick, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…McLaughlin et al (1982) demonstrated that a higher proportion of photosynthate remained in the foliage and branches of white pine following exposure to ozone, and less was exported to the bole and the roots. McLaughlin & McConathy (1983) proposed that ozone might cause a malfunction in the phloemloading process, increasing the allocation of photosynthetically fixed carbon to repair damage at source. Hanson & Stewart (1970) were able to show that ozone could delay starch hydrolysis and stimulate respiration which down-regulated photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ozone might reduce photosynthesis (Reich & Amundson, 1985;Dann & Pell, 1989;Edwards, Wullschleger & Kelly, 1994) and yield (Heck et al, 1983), and alter carbon allocation (Cooley & Manning, 1987;Letchworth & Blum, 1977;McLaughlin et al 1982;McLaughlin & McConathy, 1983) in higher plants. However, most research to date on the plant physiological responses to ozone has focused on economically important fastgrowing crops and on forestry species.…”
Section: Introductionmentioning
confidence: 99%
“…()., and SOj are both ktiowti to reduce root/shoot ratios (Tingey, Heck & Reinert, 1971 ;Okano et al, 1984;Godzik, Ashmore & Bell, 1985), with O., having larger effects on this parameter (McLaughlin & McConathy, 1983). This is mediated through the leaf, as O., does not directly affect below ground parts of the plant (Blum & Tingey, 1977).…”
Section: Nature Of Resistancementioning
confidence: 99%